Strengthening Cyber Resilience Against Online Scamming Threats Through Optimizing Police Human Resources and Digital Literacy Campaigns (International Journal of Environmental Sciences, 2025)
This research is motivated by the increase in cybercrime in the digital era, which poses complex challenges for law enforcement, data security, and community protection. This problem is exacerbated by a lack of adequate regulation and technical constraints in law enforcement. This research is aimed at identifying and developing a model for optimizing the National Police's human resources through the establishment of special units and digital forensic training to strengthen law enforcement against online scamming crimes, and formulate effective digital literacy campaign strategies to increase public awareness of the threat of online scamming, in order to reduce vulnerability and support national cyber resilience. The analysis knife of this research uses Cyber Law Theory, Institutional Capacity Theory, Transnational Crime Theory, Digital Literacy Theory, and Multi-Stakeholder Collaboration Theory. This research is a literature study research that is descriptive-analytical. This approach allows for the identification of patterns, challenges, and opportunities in the handling of cybercrime, without involving the collection of primary data such as surveys or field interviews. Data analysis was carried out through the qualitative analysis content method. The results of this study show that the development of the National Police's human resource optimization model to deal with online scamming crimes involves the establishment of a special unit of the Ditressiber in each Regional Police, AI-based digital forensic training and big data analytics, as well as integration with various parties by adopting global best practices such as the Anti-Scam Command Singapore and IC3 AS to detect and handle phishing, deepfakes, and crypto transactions. Digital literacy strategies are implemented through social media, workshops, and technologies such as mobile applications, aimed at increasing public awareness, especially the elderly and MSMEs, to reduce vulnerability and financial losses and support national cyber resilience. The conclusion of this study is that handling cybercrime requires an integrated approach that involves cross-sectoral collaboration, strengthening regulations, and improving digital literacy. Law enforcement strategies must be supported by advanced technology and an adaptive cross-border legal framework, to minimize the risk of cybercrime and protect society in the digital age.